Studies on thermo mechanical and surface properties of polysulfone/poly(ether imide ester) blends. (2019) - James Jose, Ajith; Wilson, Runcy; Jacob, George; Alagar, Muthukaruppan
Abstract: Polyimides are high performance polymeric materials with excellent physical, thermal and mechanical properties, but its application is limited due to low processability and poor solubility. In order to improve processability and solubility without sacrificing thermal stability, flexible linkages such as ether and ester units were incorporated into the polyimide backbone. Poly (ether imide ester)s were prepared by high temperature solution polycondensation reaction. The blends of polysulfone (PSf) and poly (ether imide ester) were prepared by solution casting method. The effect of blend ratio on morphological, hydrophilic, mechanical and thermal properties of the resultant blends were evaluated. Thermal properties of the blends were analyzed using thermo gravimetric analysis and differential scanning calorimetry. The contact angle measurements was carried out to study the influence of poly (ether imide ester) in corporation on the wettability of the of PSf matrix. Various surface parameters such as total surface free energy, interfacial free energy, work of adhesion, spreading coefficient and Girifalco-Good's interaction parameter were calculated from the measured contact angle values.